The The first report of pure neuritic leprosy with involvement of the anterior femoral cutaneous nerve - Francisco Bezerra de Almeida Neto; Raul Aureliano Neto; Lucas Machado Carvalho Cardoso (MDPI AG, 2019)
We describe the case of a young man, 22 years old, a household contact of leprosy, presenting paresthesia in the right leg and great thickening in the anterior femoral nerve and in the ipsilateral sural nerve. There were no typical dermatological lesions of leprosy. Ultrasonography confirmed the clinical finding. The clinical diagnosis of the disease was established and the patient started multibacillary-multidrug therapy, obtaining improvement of the initial symptomatology.